Biological Flora of the British Isles: Eryngium maritimum. (May 2014) - Isermann, Maike; Rooney, Paul
Summary This account presents information on all aspects of the biology of Eryngium maritimum L. (Sea Holly) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history and conservation. Eryngium maritimum is a native perennial hemicryptophyte, with a large taproot, spiny and leathery leaves and a pale bluish inflorescence. It has a more or less continuous distribution in suitable habitats along the coasts of Great Britain and Ireland up to about 55° N, but it is more scattered further north. On the west coast, it is found south of the Hebrides, and on the east coast, with some exceptions, south of Yorkshire. In Europe, it has a wide, but mainly southern temperate, European distribution along the coasts of the Atlantic Ocean, the Baltic, the Mediterranean, and the Black and Azov Seas. Its northern distribution limit is at c. 60° N. Eryngium maritimum grows typically on sand and shingle beaches, foredunes and yellow dunes, as well as in semi‐fixed grey dunes. Its habitats have full sunlight and are more or less dry. It occurs in many coastal plant communities from the beach inland, and because of its wide European distribution, it occurs with members of several different biogeographical species groups. Protected from grazing by its spininess and sclerophylly, E. maritimum is nevertheless vulnerable to direct damage by trampling. It supports few insect herbivores, probably because of chemical defences. Historically, it has had a great number of medicinal uses. Eryngium maritimum is unable to withstand competition from faster and more densely growing plant species. In many coastal regions, in both temperate and mediterranean parts of Europe, it is one of the rarest and most threatened plant species, mainly because of habitat loss and land‐use changes.